2016
DOI: 10.1038/srep30260
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific genetic and antigenic variations of influenza A viruses in Hong Kong, 2013–2014

Abstract: Age-specific genetic and antigenic variations of influenza viruses have not been documented in tropical and subtropical regions. We implemented a systematic surveillance program in two tertiary hospitals in Hong Kong Island, to collect 112 A(H1N1)pdm09 and 254 A(H3N2) positive specimens from 2013 to 2014. Of these, 56 and 72 were identified as genetic variants of the WHO recommended vaccine composition strains, respectively. A subset of these genetic variants was selected for hemagglutination-inhibition (HI) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…From another aspect, our study revealed that the odds of being infected with A(H1N1)pdm09 among adults was higher than in infants and children ≤ 6-year-old, while the odds of being infected with A(H3N2) was higher in infants and children ≤ 6-year-old. Nevertheless, The relationship between age and infection with a specific influenza A subtype is a matter of inconsistencies between different reports, which may vary with season, epidemic timing, lack of pre-existing immunity against novel A(H3N2), and study settings [31, 32]. In our case, this result could be attributed to the limitation of our study in regard to the number of samples collected in these different groups and the months of collection.…”
Section: Discussionmentioning
confidence: 72%
“…From another aspect, our study revealed that the odds of being infected with A(H1N1)pdm09 among adults was higher than in infants and children ≤ 6-year-old, while the odds of being infected with A(H3N2) was higher in infants and children ≤ 6-year-old. Nevertheless, The relationship between age and infection with a specific influenza A subtype is a matter of inconsistencies between different reports, which may vary with season, epidemic timing, lack of pre-existing immunity against novel A(H3N2), and study settings [31, 32]. In our case, this result could be attributed to the limitation of our study in regard to the number of samples collected in these different groups and the months of collection.…”
Section: Discussionmentioning
confidence: 72%
“…197 Using net charge as a model for cellular binding avidity, the first question we were interested in was whether or 198 not adaptation of influenza binding avidity is present among humans of different ages. Multiple studies have 199 suggested that age-specific immune experience exists, but to our knowledge, no age-specific viral traits have yet 200 been found ( [16], [41]). Binding avidity was found to have a strong age effect in our study using net charge as a 201 proxy.…”
mentioning
confidence: 98%